A Study Of The Standard Tool For Prakritiassessment In Indigenous Medicine - Vinotha, S. (World Journal of Pharmaceutical Research, 2019)
Prakriti (Psycho-somatic constitution of the body) is specific composition of humors (dosha) that is permanent throughout the life. The psycho-somatic type of an individual depends on the tribasic functional factor (vata, pitta, or kapha) that dominates in the reproductive elements sperm and ovum (sukillam and sonitam) during conception. A good knowledge of prakriti is essential for the treatment and management. Therefore, in the present study was developing the standard tool for Prakriti assessment based on considering several aspects of the body constitutions in Indigenous Medicine. It is a Descriptive literature review related study was conducted from November 2011 to January 2012. Data were collected from the related past and recent Traditional text books and other documents from Jaffna/ Sri Lanka. Prakriti Assessment tool was developed by considering only thirty-three selected categories, and 60 subdivisions. This standard Prakriti assessment tool developed in this present study to be confirming the correct Prakriti. Hence, the developed assessment tool can be used not only in the health volunteers but also in clinical practices for the clinical validation.
Keywords: Prakriti; Standard tool; Indigenous Medicine